2010
DOI: 10.1186/1471-2407-10-693
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of quantitative diffusion-weighted MR imaging in the differential diagnosis of breast lesions

Abstract: BackgroundTo determine, in a meta-analysis, the diagnostic performance of quantitative diffusion-weighted (DW) MR imaging in patients with breast lesions.MethodsEnglish and Chinese studies published prior to June 2009 to assess the diagnostic performance of quantitative DWI in patients with breast lesions were reviewed and summarized with reference to the inclusion and exclusion criteria. Methodological quality was assessed by using the quality assessment of diagnostic studies (QUADAS) instrument. Publication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
156
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(167 citation statements)
references
References 36 publications
6
156
3
2
Order By: Relevance
“…It is well known that the calculated ADC value is clearly affected from the scanning parameters. Therefore, previous studies using different scanning parameters reported different cutoff values for the discrimination of malignant and benign tumors (13,(21)(22)(23). In our practice, we routinely apply DWI as a part of our standard breast MRI protocol and as ADC threshold we use 0.90 ×10 -3 mm 2 /s, which is the cutoff value that was obtained from our previous DWI study (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the calculated ADC value is clearly affected from the scanning parameters. Therefore, previous studies using different scanning parameters reported different cutoff values for the discrimination of malignant and benign tumors (13,(21)(22)(23). In our practice, we routinely apply DWI as a part of our standard breast MRI protocol and as ADC threshold we use 0.90 ×10 -3 mm 2 /s, which is the cutoff value that was obtained from our previous DWI study (15).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, diffusion weighted imaging (DWI) is a newly proposed and highly effective MRI technique used for characterization of breast lesions, especially of masses, by measuring the random motion of free water protons in tissues. DWI is easy to evaluate, does not require contrast injection, has short imaging time and shows higher specificity (reported to be 84% in a meta-analysis) than DCE imaging (13).…”
mentioning
confidence: 99%
“…DCE-MRI of the breast provides high-resolution anatomic information and enables the depiction of increased microvascular density and capillary leaks in malignant breast tumors as a marker of neoangiogenesis (29). DWI depicts cellular diffusivity, which is typically restricted in malignant tissue (7,20). 3D 1 H-MRSI detects elevated levels of the metabolite choline as a marker of an increased cell membrane turnover (6).…”
Section: Discussionmentioning
confidence: 99%
“…MP MRI provides morphologic and functional information that results in a high sensitivity and improved specificity (5)(6)(7)(8). 18 Fluorodeoxyglucose ( 18 FDG)-PET provides functional data on tumor metabolism and has been found to be of complementary value (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of thirteen studies evaluating the diagnostic performance of ADC in quantitative breast DWI from 964 lesions (615 malignant and 349 benign) demonstrates that pooled mean ADC from malignant lesions is significantly lower than that of benign lesions that may range from 0.87 to 1.61×10 (27). In the current study, ADC estimations are performed by nonlinear fitting the mono-exponential model to average lesion signal intensity data to ensure high precision in the estimates (use of commonly preferred linear fitting complemented with log transformation in ADC estimations is reported to lower the precision (28)).…”
Section: Discussionmentioning
confidence: 99%